PERANCANGAN SISTEM PENGOLAHAN DATA PENYULUH AGAMA DI KECAMATAN BANYUMAS BERBASIS WEBSITE - Zulkifli Zulkifli; Tri Ayu Septiana; Sodikin Sodikin; Andino Maseleno (LPPM STMIK Pringsewu, 2018)
Extension worker of Islamic Religion is a profession that became the spearhead in syiar Islam Religion either functional or honorer or even volunteer. The management faced is increasingly complex with the development of the era of all-digital (modern). The purpose of this research is to design an information system about religious education activities in Banyumas Subdistrict especially related to data processing of target institution or group target, management of activity schedule and extension agenda, guidance and consultation activity, and making final report of performance target of religious instructor. This study uses data collection techniques through observation and documentation interviews to obtain data more clearly in accordance with the required in the study. In this study produce a website-based data processing system that can be used Banyumas District Government to conduct pengelolahan data extension religion in the District Banyumas. It is expected that this system can facilitate the work of religious instructors in Banyumas Subdistrict in terms of managing, organizing and organizing religious education activities that take place to be faster, accurate and computerized in real time.